No rastro dos Dragões: políticas da ordem e o universo militar nas Minas setecentista - Francis Albert Cotta Formiga (2004)
This is a study of the instrumentalization of Portuguese public safety policies in eighteenth-century Minas Gerais by way of th deployment of military corps throughout the captaincy. Initially an attempt is made to better understand the significance of the term police during the period and how that concept was related to the implementation of policies in Portuguese America. According to the Portuguese conception, police was the order established for the safety and public convenience of the people. Strong military traditions in tandem with the fragility of civil institutions involved in policing are seen to have reinforced the use of the armed forces in maintaining public order. Given the geopolitical and economic characteristics of Minas Gerais, from the very beginning of the eighteenth century military corps specialized in social control and the preservation of public peace and tranquility were formed. Following a corporative military system the Dragões, Ordenanças, Auxiliares, Homens-do-mato and Pedestres, whether acting in an integrated fashion or independently, were responsible for executing policies of public safety in the towns, villages and backlands. In Minas the military system, marked as it was by a complex and contradictory repertory of collective and individualistic practices, succeeded in keeping violence down to acceptable levels and in facilitating tax collection and the economic development of the region